Studies on Glycosaminoglycans Isolated from Bivalves Molluscs Tridacna maxima and Perna viridis - Arumugam, M.; Balasubramanian, T.; Warda, M.; Linhardt, R.J. (Our Nature, 2010)
The glycosaminoglycans (GAGs) in two marine invertebrate molluscs such as Tridacna maxima and Perna viridis were analyzed. Both the species was found to contain variable amounts of GAGs in the form of heparin biomolecules as identified by metachromatic activity and agarose gel electrophoresis analysis. Anticoagulant property of the biomolecules was assessed by anti factor Xa activity. Their molecular weight was estimated as 15000 and 9000 Daltons through GPC-HPLC. The 1HNMR analysis of heparin was used to predict binding sites of the heparin. Structural characterization studies clearly demonstrated that heparin is the major GAGs constituents in the test animals. Key words: Anticoagulant, Bivalves molluscs, Glycosaminoglycans, Heparin, Invertebrates DOI: 10.3126/on.v7i1.2548 Our Nature (2009) 7:10-17